2018
DOI: 10.1155/2018/9394060
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Serum Ferritin in Diagnosing Iron Deficiency in Inflammatory Conditions

Abstract: Patients with inflammatory conditions such as inflammatory bowel disease (IBD), chronic heart failure (CHF), and chronic kidney disease (CKD) have high rates of iron deficiency with adverse clinical consequences. Under normal circumstances, serum ferritin levels are a sensitive marker for iron status but ferritin is an acute-phase reactant that becomes elevated in response to inflammation, complicating the diagnosis. Proinflammatory cytokines also trigger an increase in hepcidin, which restricts uptake of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
241
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(249 citation statements)
references
References 111 publications
(138 reference statements)
3
241
0
5
Order By: Relevance
“…Anemia was categorized into mild anemia (Hb <13.5 g/dl in men or <12 g/dl in women), moderate anemia (Hb <10 g/dl) and severe anemia (Hb <8 g/dl). As recently proposed for inflammatory conditions [29,30], IDA was defined as anemia (Hb levels beneath gender-adjusted lower limit of normal) together with a ferritin concentration <100 µg/L or transferrin saturation <16%. The PHG was classified by experienced endoscopists according to consensus guidelines [31] in three groups: no PHG, mild PHG, and severe.…”
Section: Endoscopy and Laboratory Datamentioning
confidence: 99%
“…Anemia was categorized into mild anemia (Hb <13.5 g/dl in men or <12 g/dl in women), moderate anemia (Hb <10 g/dl) and severe anemia (Hb <8 g/dl). As recently proposed for inflammatory conditions [29,30], IDA was defined as anemia (Hb levels beneath gender-adjusted lower limit of normal) together with a ferritin concentration <100 µg/L or transferrin saturation <16%. The PHG was classified by experienced endoscopists according to consensus guidelines [31] in three groups: no PHG, mild PHG, and severe.…”
Section: Endoscopy and Laboratory Datamentioning
confidence: 99%
“…To date, only four studies have been published examining the clinical value of sTfR or TfR‐F in detecting iron deficiency in IBD 23 . Although these studies 20,23‐25 showed that iron deficiency detection rates with sTfR or TfR‐F are higher than the commonly used markers TfS and ferritin, sTfR is rarely used in routine practice by IBD physicians due to high costs and low availability. The aims of this study were to evaluate the accuracy of currently recommended TfS and/or ferritin cut‐offs for the diagnosis of iron deficiency, using sTfR as the reference due to the inflammation that is present in IBD patients, and to identify the optimal thresholds to predict iron deficiency in a large cohort of patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The FMF patients were divided into two subgroups as FMF‐I (+) or FMF‐I (−) according to presence or absence of inflammatory response, as indicated by elevated erythrocyte sedimentation rate and elevated C‐reactive protein (CRP) level. Functional iron deficiency and AID were defined in accordance with the description of iron status, CBC parameters, and CRP level . Absolute iron deficiency was defined as transferrin saturation <20% and ferritin levels <30 ng/mL in association with normal CRP level.…”
Section: Methodsmentioning
confidence: 99%
“…This form of deficiency occurs when there is insufficient iron transport into erythroid precursors despite sufficient body stores of iron during inflammation. Distinct from FID, absolute iron deficiency (AID) is characterized by low iron stores in patients without inflammation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation